Takeover defenses in the era of shareholder activism - SHIN, Sa-Pyung Sean (Institutional Knowledge at Singapore Management University, 2016)
This paper examines the interplay between takeover defenses and shareholder activism. Using a comprehensive sample of shareholder activism events between 2006 and 2014, I find a differential impact of takeover defense measures on the likelihood of being targeted for activism; a dual-class structure or a staggered board deters activism, whereas firms with a poison pill in place are more likely to become targets. Activists are more likely to demand removal of takeover defense measures and/or sale of the target firm if the firm has a staggered board or a poison pill in place, suggesting that when takeover defenses block the market for corporate control, activists promote changes through their interventions. I also find that target firms with takeover defenses are more likely to remove those defenses and more likely to be acquired following activism, which suggests that activism can act as an antidote to takeover defenses. Finally, while many target firms adopt a poison pill in response to activist approaches, I do not find evidence that it makes for an effective defense.